Development of new media formulation for the improvement of recombinant protein expression in E.Coli - Mohd. Salleh, Hamzah; Hashim, Yumi Zuhanis Has-Yun; Nuge, Tamrin (s.n, 2012)
The optimum growth media for the recombinant protein expression has the added advantage of improved cost effectiveness, enhanced down-stream processing, reduced wastewater, lower production costs and reduced investment in equipment. In this study a series of statistical optimization involves screening, classical optimization (OFAT) and response surface methodology (RSM) is employed to develop an optimum media for bacteria growth. E. coli DH5 harboring phytase gene from Mycobacterium smegmatis is used as a model to develop the modified growth media. At the end of the study, the effectiveness of the newly developed growth media was also tested on few recombinant proteins.